REVITALIZATION OF MARGA MULYA VILLAGE’S FLAGSHIP PRODUCTS THROUGH ENVIRONMENTALLY FRIENDLY PACKAGING INNOVATION AND DIGITAL SALES STRATEGIES - Arief Bowo Prayoga Kasmo; Diah Fistiani Sukardiman; Novena Ulita; Muhammad Raafi Hillal Atha'Ullah Azmi; Meisya Putri; Ravel Setyo Bintoro (Universitas Muhammadiyah Tangerang, 2025)
Marga Mulya Village, located in Mauk Subdistrict, Tangerang Regency, possesses considerable potential for the development of home-based industries, particularly fish crackers and handicraft products. However, this potential has not been optimally realized due to limitations in packaging innovation, digital marketing strategies, and brand management. This Community Service Program aims to enhance the competitiveness of the village’s flagship products through the introduction of environmentally friendly packaging and the implementation of digital marketing strategies. The program employed a collaborative participatory approach, encompassing stages of socialization, training, technology implementation, mentoring, and evaluation. The results demonstrate significant improvements in both production and marketing aspects, including the creation of eco-friendly packaging innovations, the establishment of business social media accounts and online stores, and the development of digital catalogs for the village’s flagship products. The program confirms that packaging innovation and the digitalization of marketing can increase revenue, strengthen branding, and promote the sustainability of the local economy.